2015
DOI: 10.1590/2359-3997000000053
|View full text |Cite
|
Sign up to set email alerts
|

Circulating E-selectin levels and insulin resistance are associated with early stages of atherosclerosis in nonfunctional adrenal incidentaloma

Abstract: Objective: To evaluate circulating E-selectin levels in patients with nonfunctional adrenal incidentaloma (NFA) in relation to insulin resistance and early atherosclerosis. Subjects and methods: A total of 40 patients with NFA (mean [SD] age: 55.6 [10.7] years; 70% were females) and 35 controls (mean [SD] age: 51.5 [8.1] years; 71.4% were females) selected from age-, gender-and body mass index (BMI)-matched healthy subjects were enrolled. Serum hsCRP, lipid profile, insulin levels and the homeostasis model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Both lipid deposition on the vessel wall and smooth muscle migration is closely related to time, and the occurrence has shown a significant time dependence. As age increases, changes in cells, enzymes, molecules, and other substances in the vascular wall will cause reduced vascular (19,20). Moreover, in the results of this study, the difference in TPS and SSS between different age groups was also statistically significant, and the older the age, the higher the score and the greater the degree of stenosis.…”
Section: Discussionsupporting
confidence: 52%
“…Both lipid deposition on the vessel wall and smooth muscle migration is closely related to time, and the occurrence has shown a significant time dependence. As age increases, changes in cells, enzymes, molecules, and other substances in the vascular wall will cause reduced vascular (19,20). Moreover, in the results of this study, the difference in TPS and SSS between different age groups was also statistically significant, and the older the age, the higher the score and the greater the degree of stenosis.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast to these results, several studies have reported a significant association between E-selectin levels and CIMT. A study by Delibasi et al 27 found that in subjects with nonfunctional adrenal incidentalomas, E-selectin concentrations correlated significantly with both HOMA-IR and CIMT, while Baldassarre et al, 28 who examined subjects with only CVD but no diabetes, found that statin therapy significantly decreased both CIMT and E-selectin concentrations indicating the treatment's ability to improve endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%